2019
DOI: 10.1186/s12905-019-0848-5
|View full text |Cite
|
Sign up to set email alerts
|

No straight lines – young women’s perceptions of their mental health and wellbeing during and after pregnancy: a systematic review and meta-ethnography

Abstract: BackgroundYoung mothers face mental health challenges during and after pregnancy including increased rates of depression compared to older mothers. While the prevention of teenage pregnancy in countries such as the United States and the United Kingdom has been a focus for policy and research in recent decades, the need to understand young women’s own experiences has been highlighted. The aim of this meta-ethnography was to examine young women’s perceptions of their mental health and wellbeing during and after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 75 publications
2
30
0
Order By: Relevance
“…As qualitative studies proliferated, reviewers from nursing and other disciplines began targeting subgroups or specific experiences of teen mothers such as breastfeeding (MacVicar et al, 2015), homelessness (Meadows-Oliver, 2006), and those who experienced partner violence (Bekaert & SmithBattle, 2016) or foster care (Connolly et al, 2012). Other reviews addressed mothers’ perspectives on mental health (Lucas et al, 2019), the transition to parenting (Anastas, 2017), pregnancy intention (Macutkiewicz & MacBeth, 2017), and schooling (Peterson & Bonell, 2018). Anastas (2017) reviewed primary studies to categorize how teen mothering was framed as a problem located in the teen, her family, or society.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As qualitative studies proliferated, reviewers from nursing and other disciplines began targeting subgroups or specific experiences of teen mothers such as breastfeeding (MacVicar et al, 2015), homelessness (Meadows-Oliver, 2006), and those who experienced partner violence (Bekaert & SmithBattle, 2016) or foster care (Connolly et al, 2012). Other reviews addressed mothers’ perspectives on mental health (Lucas et al, 2019), the transition to parenting (Anastas, 2017), pregnancy intention (Macutkiewicz & MacBeth, 2017), and schooling (Peterson & Bonell, 2018). Anastas (2017) reviewed primary studies to categorize how teen mothering was framed as a problem located in the teen, her family, or society.…”
Section: Resultsmentioning
confidence: 99%
“…Regardless of the discipline of the authors and the aims of the reviews, the transformative power of mothering was apparent from the earliest (Clemmens, 2003) to the most recent primary review (Lucas et al, 2019), and across vulnerable subgroups including teen mothers who were homeless (Meadows-Oliver, 2006); had experienced violence (Bekaert & SmithBattle, 2016); or had spent time in foster care (Connolly et al, 2012). Reviewers referred to this transformational potential with language and metaphors describing how mothering provides meaning and fulfillment, and serves as a catalyst for becoming mature, reducing risky behavior, repairing relationships, reinventing the self, and seeking a better life anchored by the baby (Clemmens, 2003; Erfina et al, 2019; Graham & McDermott, 2005; Lucas et al, 2019; Meadows-Oliver, 2006) precisely because teens who became mothers lacked options for gaining meaning and independence (McDermott & Graham, 2005, p. 75). On the background of social disadvantage and difficult childhoods, and with few avenues for developing other identities, mothering was rewarding, provided purpose, and filled an emotional void (Bekaert & SmithBattle, 2016; Connolly et al, 2012; Macutkiewicz & MacBeth, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…During pregnancy and childbirth, parturient women often experience both physical and psychological changes, resulting in a significantly increased probability of mental problems after childbirth [16]. Clinical studies have shown that sudden changes in social roles of women after childbirth, coupled with rapid changes in social relationships and functions, exacerbate negative emotions such as anxiety and depression, leading to recurring unhealthy mental states [17]. Among these unhealthy mental states after delivery, postpartum depression is a common, disabling and treatable reproductive complication [18].…”
Section: Discussionmentioning
confidence: 99%